2006
DOI: 10.1002/art.21631
|View full text |Cite
|
Sign up to set email alerts
|

PUMA regulation and proapoptotic effects in fibroblast‐like synoviocytes

Abstract: Objective. Although p53 is overexpressed in rheumatoid arthritis (RA) synovial tissue (ST), few synoviocytes undergo apoptosis. This could be partly due to low expression of proapoptotic genes. Deficient p53 upregulated modulator of apoptosis (PUMA), which is a major effector of p53-mediated cell death, could contribute to this phenomenon. To evaluate a method to induce apoptosis, the expression and function of PUMA was investigated in ST and cultured fibroblast-like synoviocytes (FLS).Methods. PUMA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 15 publications
1
47
0
1
Order By: Relevance
“…It has been shown that the levels of p45 up-regulated modulator of apoptosis (PUMA; or, Bcl-2-binding component 3 ), which is a downstream effector of p53-mediated apoptosis, are low in FLS, and this has been proposed to contribute to the low apoptosis in the synovial intimal lining (36). As with BNIP-3 (29), PUMA is also a BH3 proapoptotic Bcl-2 family member that interacts with the antiapoptotic Bcl-2/Bcl-x L , this in turn, promoting mitochondrial dysfunction and cell death through Bax/Bak.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the levels of p45 up-regulated modulator of apoptosis (PUMA; or, Bcl-2-binding component 3 ), which is a downstream effector of p53-mediated apoptosis, are low in FLS, and this has been proposed to contribute to the low apoptosis in the synovial intimal lining (36). As with BNIP-3 (29), PUMA is also a BH3 proapoptotic Bcl-2 family member that interacts with the antiapoptotic Bcl-2/Bcl-x L , this in turn, promoting mitochondrial dysfunction and cell death through Bax/Bak.…”
Section: Discussionmentioning
confidence: 99%
“…Repression of AHR expression was achieved using small interfering RNA (siRNA) (Dharmacon siRNA, control oligo D-001810-0X, AHR oligo J-004990-07; Pittsburgh, PA). Cells were electroporated with siRNA using the U-020 program of Amaxa nucleofection system (Lonza, Walkersville, MD) as previously described (Cha et al, 2006;Dinatale and Perdew, 2010). Transfected cells were seeded into six-well plates at 2 Â 10 6 cells/well synoviocyte growth media.…”
Section: Methodsmentioning
confidence: 99%
“…Exogenous p53 overexpression induced p21, but not Puma in FLS and this was associated with resistance of FLS to apoptosis. However, transfection of plasmid encoding Puma expression vector lead to rapid and profound apoptosis with caspase-3 activation in RA FLS (Cha et al, 2006). Tissue-and cell type-specific selectivity of p53 in transactivation of downstream genes has been reported (Fei et al, 2002).…”
Section: Introductionmentioning
confidence: 99%